X-ray powder diffraction study on the MgB2 superconductor with nano-SiC additions: The effects of sintering temperature - Tan, Kwee Yong; Tan, Kim Lee; Abdul Halim, Shaari; Tan, Kar Ban; Chen, Soo Kien (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia.